2015
DOI: 10.1002/14651858.cd008884.pub2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of high perioperative inspiratory oxygen fraction for adult surgical patients

Abstract: The e ects of high perioperative inspiratory oxygen fraction for adult surgical patients (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
2
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 127 publications
(11 reference statements)
6
75
2
9
Order By: Relevance
“…There is a separate body of evidence, mostly in the elective surgical setting 18. There is an unresolved debate about whether supplemental oxygen reduces the risk of surgical site infections.…”
Section: Understanding the Recommendationsmentioning
confidence: 99%
“…There is a separate body of evidence, mostly in the elective surgical setting 18. There is an unresolved debate about whether supplemental oxygen reduces the risk of surgical site infections.…”
Section: Understanding the Recommendationsmentioning
confidence: 99%
“…This positive outcome corresponds to the Cochrane review of Wetterslev et al 88 Here, they also concluded that high supplemental inspired oxygen during colorectal and abdominal surgery decreases the risk of SSIs. 88 However, a large trial of Meyhoff et al, that investigated high-inspired oxygen during abdominal surgery showed no differences in SSIs rates between patients receiving 30 and 80% oxygen. 89 Although this randomized clinical trial included a great amount of various types of abdominal surgical procedures, they did not investigate the risk of SSI for every surgical procedure separately.…”
Section: Supplemental Inspired Oxygenmentioning
confidence: 99%
“…1,2 Only recently, perioperative hyperoxia has been associated with higher patient mortality and morbidity although the detailed injurious mechanisms remain unknown. [3][4][5][6] While the effects of constant hyperoxia on the human body have been investigated to some extent, little is known with regard to cyclic hyperoxia that may occur during O 2 -administration in the presence of altered cardiac or pulmonary function. For example, cyclic hyperoxia can be caused by cyclic recruitment and derecruitment of lung atelectasis (cyclic atelectasis, CA) during high-dose O 2 -administration.…”
Section: Editorial Comment: What This Article Tells Usmentioning
confidence: 99%
“…39 However, recent studies have questioned a net beneficial effect of hyperoxia that seems associated with increased mortality and morbidity. [4][5][6] The mechanisms by which hyperoxia may harm the human body include increase in reactive O 2 -species, reduced organ blood flow, and disturbances in cellular redox balance. 1,2 The present study adds a novel concept to this topic by proposing that extreme constant and cyclic hyperoxia potentially may cause harm to the vascular endothelium by signaling pathways including the oxidative stress, NFjB, Notch, and PPAR pathway.…”
Section: Clinical Relevancementioning
confidence: 99%